Management of Natural Resources, Sustainable Development and Ecological Hazards III 2011
DOI: 10.2495/rav110301
|View full text |Cite
|
Sign up to set email alerts
|

Environmental friendly concrete production using municipal solid waste incineration materials

Abstract: The building industry, especially construction materials' production, is a major user of the world's resources and together with energy production one of the most important sources of the CO 2 production. Among building materials, concrete is element which is the second most consumed substance in the world, whereas only water is used in greater quantities. Apparently, almost one ton of concrete is used for each person in the world each year. From the point of view of ecological and sustainable aspects, concret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…One study showed that higher mortar strengths resulted with up to 10% mass replacement of Portland cement by MSW fly ash (Goh C.C., et al, 2003), whereas another only found that partial replacement up to 10% mass does not significantly affect the compressive strength of cement and mortar (Siddique R., 2010); a third found that MSW fly ash has some cementitious activity, but "the reactivity is relatively lower" (Shi H., et al, 2006). Another stated that three different MSW fly ashes all "made the mortars properties worse" (Pavlik Z., et al, 2012). All studies found that MSW fly ash addition to cement significantly increases the setting time (Hamernik J.D.…”
Section: Use Of Energy From Waste Air Pollution Control Residues In Bmentioning
confidence: 99%
“…One study showed that higher mortar strengths resulted with up to 10% mass replacement of Portland cement by MSW fly ash (Goh C.C., et al, 2003), whereas another only found that partial replacement up to 10% mass does not significantly affect the compressive strength of cement and mortar (Siddique R., 2010); a third found that MSW fly ash has some cementitious activity, but "the reactivity is relatively lower" (Shi H., et al, 2006). Another stated that three different MSW fly ashes all "made the mortars properties worse" (Pavlik Z., et al, 2012). All studies found that MSW fly ash addition to cement significantly increases the setting time (Hamernik J.D.…”
Section: Use Of Energy From Waste Air Pollution Control Residues In Bmentioning
confidence: 99%